The Effectiveness of Smart City Program Through Batu Among Tani Teknologi (BATT) in Batu City, Indonesia - Iradhad Taqwa Sihidi; Mochamad Aan Sugiharto; Laeli Nurkhanifah (Universitas Muhammadiyah Gorontalo, 2021)
This paper explains the effectiveness of implementing the Batu Among Tani technology (BATT) program in Batu City. BATT itself is one of the leading smart city concepts of the Batu City Government, which aims to protect and develop agricultural quality. BATT is here to solve some of the fundamental problems of agriculture in Batu City, focusing on harvests, brokers’ intervention, lack of agricultural information, and several other complaints. This research uses qualitative research with a descriptive approach—sources of data obtained through interviews with relevant stakeholders and observations and documentation. Data is processed through data collection, data reduction, data display, and conclusion drawing. The results showed that the BATT Program, which began running effectively in September 2017, was not optimal. First, the server capacity is limited so that it often experiences interruptions and the benefits of services provided are less than optimal. Second, the lack of participation of farmers as active users of BATT. The factor of the lack of outreach and ongoing assistance is the cause. Third, the program has not effectively delivered price updates and cut off the brokers' intervention chain. However, this program is criticized for converting agricultural land to non-agriculture for the past 5 (five) years in Batu City.